Incorporation of the Sociocultural Heritage as an Essential Component in the Emergy Assessment of Agroecological Systems in the Central Region of Valle del Cauca-Colombia - iguez, Judith Rodr '; Sanchez, Marina; no, Angela M. Londo; noz, Johana S. Mu (Journal of Environmental Accounting and Management, 2026)
In Valle del Cauca, a wide range of agroecological production systems havebeen preserved, withstanding the expansionist onslaught of sugar cane monoculture. The study performed the emergy assessment to three agroecological farms in the municipalities of Andalucia, Sevilla and Buga, incorporating a novel flow of emergy called Sociocultural Heritage (H), which is determinant for the functioning of the agroecological farms in the Colombian context, which includes the contribution of internal family labor given by their permanent residence in the agroecosystem, the family's activity to promote agroecological culture with external actors to the farm, the memory of information, and the appropriation of knowledge. The identity architecture and management of the agrosystem were expressed by the total emergy (U), computing the emergy flows of: renewable natural resources (R), nonrenewable (N), Sociocultural Heritage (H), purchased materials (M), and contrated services (S). The efficiency of agroecological farms, involved inclusive emergetic indices that contain the Sociocultural Heritage (H): Percentage of Sociocultural Heritage (%H), Inclusive Renewability (%RH) and Inclusive Environmental Burden Index (ELRH). The H flow gave results between 6,95 and 42,19 E + 17 sej / year, representing 45,47% and 55,07% of total emergy as %H. The %RH index gave values higher than 91%, indicating that the farms have a high renewability. The ELRH index presented values between 0,05 and 0,09, indicating a low environmental load of agroecological systems and low pressure of agroecological farms on local ecosystems. The results of inclusive emergetic indixes from this study show that agroecological systems are more sustainable in the long term. This would not be so evident with results obtained through an emergy assessment without the inclusion of the H.